Domain Geologi Material di Area Pit Limit Menggunakan Analisis Statistik Pada Tambang Quarry PT. Semen Padang, Sumatera Barat - Helio Gina Febriandika; Adree Octova; Della Aulia Aidil (Journals Mining Engineering : Bina Tambang, 2021)
At PT. Semen Padang mining activities carried out in an area of 206 Ha in the existing area. The remaining reserves at the existing location are estimated to be exhausted in September 2019, so PT. Semen Padang will expand its mining area to the Pit Limit and Tajarang areas. Before conducting mining activities in the Pit Limit area, it is necessary to know the geological domain of this material to find out the areas that will be mined. Geological domain is carried out using statistical analysis. Database information for the estimation of limestone, tuff, silica, soil and basalt resources in the Pit Limit area was obtained from exploration drilling activities derived from 20 drill hole data with depths ranging from 50 meters to 200 meters depth. Based on the lithology histogram in the pit limit area, we can see that the limestone content contained in the Pit Limit area is far more than other materials, so this area is economical for mining.